2013
DOI: 10.2478/acm-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Cineole, Thymol and Camphor Nasal Challenges and their Effect on Nasal Symptoms and Cough in an Animal Model

Abstract: A b s t r a c t Inhalation of aromatic vapours suppressed coughing induced by citric acid (CA) in naive animals. No data are available about their effects in an animal model with primarily up-regulated cough reflex. New data indicate that aromatic vapours suppress cough via effect on nasal sensory nerves.The aim of our study was to ascertain the efficacy of nasal application of 1,8-cineole, thymol and camphor on nasal symptoms and CA induced cough in validated model of up-regulated cough reflex. Guinea pigs (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Outside of antiviral activity, there may be some relief of symptoms of COVID-19 provided by essential oils. For example, linalool [117,118], β-caryophyllene [119,120], and 1,8-cineole [121,122] have both anti-inflammatory and antinociceptive activity; menthol [123,124], camphor [125,126], and thymol [127] have antitussive activities.…”
Section: Resultsmentioning
confidence: 99%
“…Outside of antiviral activity, there may be some relief of symptoms of COVID-19 provided by essential oils. For example, linalool [117,118], β-caryophyllene [119,120], and 1,8-cineole [121,122] have both anti-inflammatory and antinociceptive activity; menthol [123,124], camphor [125,126], and thymol [127] have antitussive activities.…”
Section: Resultsmentioning
confidence: 99%
“… 69 , 70 Due to their variable expression patterns in neurogenic inflammation, it is also suggested that TRP channels may be partly responsible for a transition from early (acute) defensive immune and inflammatory responses to chronic responses and chronic cough pathology. 21 Unlike other TRP channels, TRPM8 can mediate a decrease in capsaicin-mediated cough sensitivity in the presence of thymol and camphor, which explains the antitussive effect of these agents, 71 , 72 probably secondary to stimulation of cool receptors in the nasal cavity. 73 , 74 TRP channel variants have been linked to altered cough presentation: TRPV1 polymorphisms have been associated with decreased wheezing in a group of asthmatics 75 but a higher risk of chronic cough in both smokers and patients with occupational exposure.…”
Section: Trp Channels In Cough Neuronal Pathwaysmentioning
confidence: 99%
“…N. discolor [ 200 ], N. laevigata [ 214 ], and N. royleana [ 217 ]. Although 1,8-cineole has been shown not to have antitussive activity [ 333 , 433 ], the compound has shown efficacy in acute rhinosinusitis and alleviate headache, nasal obstruction, and rhinological secretion in a double-blind, placebo-controlled study [ 434 ]. In addition, 1,8-cineole has demonstrated ulcer-healing and gastroprotective properties in rats [ 435 ] as well as antispasmodic effects on isolated mouse ileum [ 436 ].…”
Section: The Genus Nepetamentioning
confidence: 99%